2012
DOI: 10.1088/0004-637x/748/1/66
|View full text |Cite
|
Sign up to set email alerts
|

The 2010 August 1 Type Ii Burst: A Cme-Cme Interaction and Its Radio and White-Light Manifestations

Abstract: We present observational results of a type II burst associated with a CME -CME interaction observed in the radio and white-light wavelength range. We applied radio direction-finding techniques to observations from the STEREO and Wind spacecraft, the results of which were interpreted using white-light coronagraphic measurements for context. The results of the multiple radio-direction finding techniques applied were found to be consistent both with each other and with those derived from the white-light observati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
38
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 38 publications
4
38
0
2
Order By: Relevance
“…We estimated the source location of the associated type II enhancement by applying radio DF and triangulation techniques to data from the Wind and STEREO radio instruments. Similar radio DF and triangulation methods were previously used to study the CME-CME interaction event on 2010 August 1 by Martínez Oliveros et al (2012b). They found evidence for a causal relationship between the type II radio burst and the CME-CME interaction.…”
Section: Introductionmentioning
confidence: 62%
“…We estimated the source location of the associated type II enhancement by applying radio DF and triangulation techniques to data from the Wind and STEREO radio instruments. Similar radio DF and triangulation methods were previously used to study the CME-CME interaction event on 2010 August 1 by Martínez Oliveros et al (2012b). They found evidence for a causal relationship between the type II radio burst and the CME-CME interaction.…”
Section: Introductionmentioning
confidence: 62%
“…Type II emissions are also used to study CME-CME interactions, a typical signature of which is an increase in the bandwidth and intensity of the type II burst (Gopalswamy et al 2001b). Martinez-Oliveros et al (2012) present an occasion of two interacting CMEs, where the type II burst appears to split into two bands with different drifting rates. Based on the study of the 2012 July 23 complex eruptions, Liu et al (2017) define a complex type II burst which is composed of multiple branches that may not all be fundamental-harmonic related.…”
Section: Introductionmentioning
confidence: 99%
“…As the current solar cycle progressed, interaction of CMEs now appears a fairly common phenomenon, in particular around solar maximum. The interacting CMEs of 2010 August 1 have been studied extensively by using primarily the STEREO white light imaging, near Earth in situ and, S-Waves radio observations Liu et al, 2012;Möstl et al, 2012;Temmer et al, 2012;Martínez Oliveros et al, 2012;Webb et al, 2013). Also, Lugaz et al (2012) have reported a clear deflection of 2010 May 23 -24 CMEs after their interaction.…”
Section: Introductionmentioning
confidence: 99%
“…(6) What are the favorable conditions for the CME's deflection and enhanced radio emission during CME-CME interaction? (Lugaz et al, 2012;Martínez Oliveros et al, 2012). In light of aforementioned questions and only a few studies reported, it is clear that the prediction of arrival time of interacting CMEs and association of remote observations of such CMEs with in situ is challenging.…”
Section: Introductionmentioning
confidence: 99%